2012
DOI: 10.1295/koron.69.283
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Physical Property of Polymers Containing an Indolocarbazole Moiety

Abstract: HP1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Interestingly, PA-4 which possessed the long bisphenol-A unit in the diamine component exhibited the highest intensity of emission. Akimoto et al described that the photoluminescence intensity of INC containing copolymer solutions increased as the INC content decreased, because of the concentration quenching caused by the condensation of intermolecular interactions derived from INC components [8,10,11]. Namely, it was suggested that the photoluminescence intensity of INC-containing polyamides would be affected by weight percentage of INC content.…”
Section: Photonic Properties Of the Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, PA-4 which possessed the long bisphenol-A unit in the diamine component exhibited the highest intensity of emission. Akimoto et al described that the photoluminescence intensity of INC containing copolymer solutions increased as the INC content decreased, because of the concentration quenching caused by the condensation of intermolecular interactions derived from INC components [8,10,11]. Namely, it was suggested that the photoluminescence intensity of INC-containing polyamides would be affected by weight percentage of INC content.…”
Section: Photonic Properties Of the Polymersmentioning
confidence: 99%
“…In our previous study, the preparations of several polymers containing INC moiety in the main chain or side chain were investigated and the thermal and photonic properties of these polymers were estimated [8][9][10][11]. 1-(4vinylbenzyl)-7-octylindolo[3,2-b]carbazole (VINC-C8), and the copolymers of VINC-C8 with styrene or methyl methacrylate were prepared by a radical polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, the preparations of several polymers containing INC moiety in the main chain or side chain were investigated and the thermal and photonic properties of these polymers were estimated [8][9][10][11][12]. 1-(4-vinylbenzyl)-7-octylindolo [3,2-b]carbazole (VINC-C8), and the copolymers of VINC-C8 with styrene or MMA were prepared by radical polymerizations, and the thermal and photonic properties were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Akimoto et al described that the photoluminescence intensity of INC containing polymer solutions increased as the INC content decreased, because of the concentration quenching caused by the condensation of intermolecular interactions between INC components [8,10,11]. Therefore, to investigate the effect of INC concentration on the photoluminescence intensity, UV-Vis absorption and photoluminescence spectra of PAAINC were measured with changing the concentrations of polymer solutions, as shown in Figure 1(c) and (d).…”
mentioning
confidence: 99%
“…However, only few studies have been reported on the synthesis of INC-containing polymers. In our previous study [7][8][9], we have investigated the synthesis of a novel monomer containing indolocarbazole moiety, 1-(4-vinylbenzyl)-7-octylindolo[3,2-b]carbazole (VINC-C 8 ), and the copolymers of VINC-C 8 with styrene were prepared by a radical polymerization. Then, it was found that the obtained copolymers showed the amorphous state and the thermal stability of the copolymers increased as the INC content increased.…”
Section: Introductionmentioning
confidence: 99%